2009
DOI: 10.1162/jocn.2009.21140
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Sound Segregation Is Enhanced in Musicians

Abstract: The ability to segregate simultaneously occurring sounds is fundamental to auditory perception. Many studies have shown that musicians have enhanced auditory perceptual abilities; however, the impact of musical expertise on segregating concurrently occurring sounds is unknown. Therefore, we examined whether long-term musical training can improve listeners' ability to segregate sounds that occur simultaneously. Participants were presented with complex sounds that had either all harmonics in tune or the second h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
109
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 32 publications
14
109
2
Order By: Relevance
“…Moreover, we did not find that our violinist cohort -who spent significantly greater time in ensembles (see ST 2) -performed any better than our pianist cohort. These results contrast with previous reports of enhanced musician performance under the demands of competing speech (Parbery-Clark et al, 2009a, 2009b, 2011Strait et al, 2012b), sources of informational masking (Oxenham et al, 2003; see footnote 10), backward masking (Strait et al, 2010), and detection of auditory objects (Zendel & Alain, 2009. Our findings also contrast with previous evidence that specific expertise with ensemble settings benefits selective attention to spatially segregated sounds (Nager et al, 2003).…”
Section: Auditory Scene Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, we did not find that our violinist cohort -who spent significantly greater time in ensembles (see ST 2) -performed any better than our pianist cohort. These results contrast with previous reports of enhanced musician performance under the demands of competing speech (Parbery-Clark et al, 2009a, 2009b, 2011Strait et al, 2012b), sources of informational masking (Oxenham et al, 2003; see footnote 10), backward masking (Strait et al, 2010), and detection of auditory objects (Zendel & Alain, 2009. Our findings also contrast with previous evidence that specific expertise with ensemble settings benefits selective attention to spatially segregated sounds (Nager et al, 2003).…”
Section: Auditory Scene Analysiscontrasting
confidence: 99%
“…Zendel & Alain (2009 have shown that musicians segregate harmonic complexes better than non-musicians and more often report hearing a harmonic as a separate auditory object when mistuned by as little as 2%. Orchestral conductors -whose primary role is to analyze, interpret, and manipulate a colossal auditory sceneshow enhanced selectivity in attending to spatially segregated auditory signals (noise bursts), when compared to both pianists and non-musicians (Nager et al, 2003).…”
Section: Auditory Scene Analysismentioning
confidence: 99%
“…Musicians have enhanced cortical responses to their primary instrument, suggesting that their listening and training experience modulates the neural responses to specific timbres (Pantev et al, 2001;Margulis et al, 2009). Likewise, musicians demonstrate greater sensitivity to timbral differences and harmonic changes within a complex tone (Koelsch et al, 1999;Musacchia et al, 2008;Zendel and Alain, 2009). Within the realm of speech, timbral features provide important auditory cues for speaker and phonemic identification and contribute to auditory object formation (Griffiths and Warren, 2004;Shinn-Cunningham and Best, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…An accurate template or perceptual anchor is considered a key element for improving signal perception and facilitates the segregation of the target voice from background noise (Mullennix et al, 1989;Ahissar, 2007). Zendel and Alain (2009) showed that musicians were more sensitive to subtle harmonic changes both behaviorally and cortically, which they interpret as a musician advantage for concurrent stream segregation-a skill considered important for speech perception in noise. In interpreting their results, Zendel and Alain (2009) postulate that the behavioral advantage and its corresponding cortical index may be attributable to a better representation of the stimulus at the level of the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…The question of how conflicting rhythmic information is processed by U n c o r r e c t e d P r o o f participants with a high degree of musical expertise, therefore, remains a promising avenue for future research using this paradigm. One possibility is that improved stream segregation in expert musicians (Zendel & Alain, 2009) may enable tracking of the musical rhythm and the out-of-phase stimulus simultaneously, leading to enhanced tracking of beat harmonics on the off-the-beat condition and a smaller difference in metrical tracking between the two conditions. Another open question is whether the ability to track rhythmic structure despite conflicting information relates to language skills.…”
Section: Discussionmentioning
confidence: 99%